Depression, anxiety, stress, and post-traumatic stress disorder among Iranian nursing caring for COVID-19 patients - Bamdad Mirab Zadeh Ardekani; Fatemeh Ghassem Boroujerdi; Shirin Esmaili Dolabinjad; Mitra Safa; Farzaneh Haji Zadeh (HUMANITAS published by Universitas Ahmad Dahlan., 2023)
COVID-19 has put great physical and psychological pressure on medical staff worldwide, including Iran. As with any other disaster, it is worth paying attention to the risk of developing depression, anxiety, stress, and post-traumatic stress disorder (PTSD) among the healthcare team. This study aimed to determine the severity of depression, anxiety, stress, and PTSD status in healthcare staff involved in treating COVID-19 patients. 400 nurses and clinical assistants in a hospital occupied in treating COVID-19 were included in the study by the incidental sampling. The demographic information questionnaire, DASS-21, and Mississippi PTSD scales were applied to data collection. The mean score of PTSD in about half of the participants is severe. The mean score of re-experience sub-scale is higher than other sub-scales. Depression and stress are significantly higher in those infected with COVID-19. There is a significant difference between various age groups regarding the lack of depression. There is a significant difference in re-experience, alexithymia, and PTSD scores between participants with various marital statuses. Therefore, the existence of depression, stress, and PTSD among medical staff would be a major concern for the health ministry to protect the mental health of society members.